Pozice nespisovných variet ve stylu nové české literatury - Peter Mareš (Stylistyka, 2020)
The tendency to operate freely with devices of all language varieties and with characteristic practices of various functional styles is one of the significant features of the literary style. This paper focuses on the vast use of non-standard language varieties, especially colloquial Czech, in modern Czech literary texts. In these texts, the elements of non-standard language occur not only as a means for creating the impression of authentic communication in everyday life, but also as a bearer of (both positive and negative) values and as a source of specific aesthetic qualities. In a short outline, the individual phases of the evolution of exploiting the non-standard language devices in Czech literary style are described and illustrated on textual examples.